Enacting national school exclusion policy at the local level in England: is it black and white? - Tawell, A (Taylor & Francis, 2023)
This paper explores education professionals’ interpretations of national school exclusion policy in England and the different ways in which schools use and do school exclusion. Drawing on semi-structured interview data collected as part of my DPhil research into the enactment of school exclusion policy in one local authority in England, I investigate the extent to which national policy is understood as a clear set of imperatives or open to interpretation, and the perceived need for consistency versus flexibility in its application. I also explore how accountability frameworks and other national and local policies, including behaviour, safeguarding, and special educational needs and disability policies, are seen to interact with and influence how decisions around school exclusion are made–specifically what and when mitigating factors are considered–and highlight other contextual dimensions (situated, professional, material and external), which are seen to weave together and influence a school’s position towards school exclusion and their sense- and decision-making. In so doing, I reveal how national school exclusion policy becomes variously recontextualised and translated into practice at the local level.